Peculiarities of the verb component of object phrases in scientific texts - Анютина, Анна Анатольевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The peculiarities of free object phrases аs compositional elements of the scientific language syntactical structure are considered in the article. The criteria characterizing object phrases are presented. The importance of semantic relations between the verb and its objects is analyzed. The most widely used models of object phrases are considered. The importance of the verb valence for the object phrase structure is paid attention to. The most frequent verbs of  the scientific language chosen for objective meaning expressing, contraction of their mtaning in scientific style constructions are analyzed.